Mechanisms of binocular integration in the mammalian primary visual cortex - Sengpiel, F (1994)
Combining the images seen by the two eyes into a single percept is one of the most challenging computational tasks that the visual cortex has to solve. The first stage at which information from the two retinae converges on individual neurons is the primary visual cortex, VI or area 17. Here, I describe anatomical segregation and interocular suppression as two mechanisms for obviating potential interocular conflict. I have studied VI of the common marmoset (Callithrix jacchus), a New World monkey, with both neurophysiological and anatomical methods. Although similar in most respects to VI of the Old World macaque, layer 4 of the normal adult marmoset has a predominance of binocular cells which corresponds to a lack of segregation of geniculo-cortical afferents into ocular dominance (OD) columns. Brief early monocular deprivation (MD) causes a physiological shift in OD towards the open eye, even when followed by long-term binocular recovery. Two marmosets subjected to 3 weeks of MD from 3 weeks of age exhibited clear afferent segregation in at least parts of VI. Brief disruption of correlated binocular inputs may have served to preserve, and probably enhance the normally transient columnar OD pattern of juvenile marmosets. I have analysed responses of single neurons in cat area 17 to binocular stimuli under conditions that result in perceptual suppression of vision in one eye in humans. In normal animals, a paradigm of binocular contour rivalry was tested. The response of a binocular cell in VI to an optimally oriented grating in one eye is powerfully depressed when gratings of very different orientation are suddenly presented to the other eye, while contours of matching orientation cause the well-known disparity-selective facilitation. However, neuronal responses to persistent rivalrous stimuli do not often exhibit spontaneous alternations between states of dominance and suppression, which might be expected in view of alternations of perceptual dominance in humans under such conditions. Whether or not suppression is triggered by rivalrous contours depends on the immediate history of visual stimulation. Binocular responses are consistently depressed below monocular control levels only when stimulation through one eye with contours of inappropriate orientation is preceded by stimulation of the other eye with a grating of optimum orientation, while there is no suppression with simultaneous stimulus onset: thus neurons display interocular control of responsiveness. In most squinting humans, single vision is maintained through unilateral or alternating suppression. In cats and monkeys that have been rendered strabismic early in life, dominant-eye responses of striate cortical neurons to optimum gratings are dramatically reduced when gratings of any orientation, whether matching or orthogonal, are presented to the non-dominant eye. Like rivalrous suppression in normal animals, this phenomenon is characterized by independence of disparity, broad spatial frequency tuning and dependence on the sequence of stimulation. I propose that reciprocal inhibition between neighbouring ocular dominance columns in VI, over a number of orientation domains, mediates interocular suppression in both normal and strabismic subjects, vetoing signals from one eye in situations that would otherwise cause double vision and confusion.